Chromobacterium violaceum: A rare opportunistic pathogen and clue for pediatric chronic granulomatous disease. Issue 2 (8th December 2022) - Barnes, Peter; Gonzales, Jesse; Hammond, Daniel
Abstract: Chromobacterium violaceum is a rare bacterium found in water and soil in tropical regions and typically presents with a localized skin infection or lymphadenitis which can progress to fulminant septicemia and even death. We describe a case of a 2‐year‐old boy with C. violaceum septicemia from a suspected skin source which was confirmed by wound, tissue and blood cultures. The discovery of this rare organism, subsequently led to the evaluation and identification of underlying chronic granulomatous disease.